National Sharia Bank vs. Bank Syariah Indonesia (BSI): The Dynamics of Competition and Collaboration - Soeharjoto Soeharjoto; Rizka Agustina (Baca Dulu Publisher, 2025)
Indonesia’s Islamic banking industry is undergoing structural transformation driven by regulatory support, digitalization, and the expansion of the halal ecosystem. The dominance of Bank Syariah Indonesia (BSI) as an incumbent and the prospective establishment of Bank Syariah Nasional (BSN) reshape the competitive landscape, creating dynamics beyond direct rivalry toward co-opetition. This study examines competition and collaboration between BSI and BSN and identifies implications for inclusion. Using a descriptive qualitative approach, the research combines literature review, policy analysis, and comparative case studies. The analysis draws on co-opetition theory, the Resource-Based View, Dynamic Capabilities, the Structure–Conduct–Performance framework, and platform ecosystem theory. The findings show that BSI’s strengths lie in operational scale, synergies, and digital maturity, while BSN offers differentiation through a digital-native model and niche community focus. Collaboration via open finance, shared services, and ecosystem partnerships can expand market reach without cannibalization, provided regulatory harmonization, digital readiness, and effective risk management.